Observation of the Normalized Difference Vegetation Index (NDVI) of different types of native vegetation in the dry season of 2011 and 2014 , in Piracicaba -SP - Tavares, Tiago Rodrigues; Fiorio, Peterson Ricardo; Martello, Maurício; Strabeli, Taila Fernanda; Barros, Pedro Paulo da Silva (Revista Hipótese, 2015)
Given this atypical drought and the fragile native vegetation of Piracicaba-SP, this study compares the NDVI through Landsat 5 (TM) and Landsat 8 (OLI) images of different vegetation types in this city in the drought of 2011 and 2014. To characterize the drought we used data of the monthly precipitation time series from 1984 to 2014 recorded at the weather station at ESALQ-USP. We also calculated the Rain Anomaly Index (RAI) for the period from January to September of the studied years. The images were processed using softwares of Geographic Information System (GIS) for the obtainment of the average NDVI values of each vegetation type after the dry period for both years. Completely randomized block design with three treatments and two blocks and Turkey test for comparison of means were used. To facilitate the visualization and interpretation of the temporal variation of NDVI, the mathematical operation of subtraction was also performed between the same fragments of the two years analyzed. It was found that the native vegetation of Piracicaba showed no temporal variation of NDVI after the drought in 2011 and 2014.